Utilisation des stratégies d'apprentissage d'une langue étrangère dans un environnement virtuel multi-utilisateurs en trois dimensions - Wen Jun Tang (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper deals with the language learning strategies in a popular multi-user virtual world, Second Life (SL). The research was based on a firsthand involvement with a group of students of Bielefeld University in Germany through participant observation, questionnaire, interview and the study of track report in the Moodle platform. According to the results, a range of metastrategies and strategies has been implemented by learners. They have encountered some major problems related to the use of SL but it has promoted mutual cooperation among them while using the target language. Despite these difficulties and the fact that they have expected to express themselves through facial expressions and body language, most students enjoyed this experience.